Mixed application of microbial fertilizers reshapes the tobacco rhizosphere microbiome and enhances metabolic coordination to improve crop quality - Lai, Xianjun; Hou, Songlin; Liu, Siqi; Zhang, Wenyou; Peng, Zhengsong; Yang, Jie; Yan, Lang; Wang, Xianjun (Frontiers in Microbiology, 2026)
Sustainable management of flue-cured tobacco requires a careful balance among productivity, chemical composition, and soil ecological function, which are often disrupted by excessive chemical fertilization. This study aimed to elucidate how microbial fertilization regulates plant performance, chemical coordination, and rhizosphere microbial structure under field conditions. A two-year factorial field experiment was conducted in Sichuan, China, using a Bacillus-based plant growth-promoting microorganism (PGPM) and a commercial microbial consortium (Xi⋅Weifeng), applied individually or in combination at gradient doses. Agronomic traits, cured-leaf chemical composition, secondary metabolites, and rhizosphere bacterial communities were comprehensively analyzed using multivariate statistics, network correlation analysis, and structural equation modeling (SEM). Moderate PGPM application (27 kg⋅ha–1) significantly increased plant height (8.6%), internode length (15.3%), and leaf width (7.8%) at the vigorous growth stage. Co-application further enhanced leaf expansion (9.7%) and improved chemical coordination, maintaining optimal sugar/nicotine (8–12) and N/nicotine (0.7–1.0) ratios. Chlorogenic acid (18.8 mg⋅g–1) and neochlorogenic acid (2.7 mg⋅g–1) were markedly elevated under the A27B54 treatment. Rhizosphere bacterial diversity peaked under co-application, with Bacillus, Rhizobiales, and Sphingomonas emerging as key taxa positively associated with both metabolic and agronomic improvements. SEM demonstrated that fertilization effects on leaf quality were mediated indirectly through microbial community restructuring and metabolite modulation. Microbial fertilizer co-application enhances tobacco performance by promoting rhizosphere microbial diversity and functional coordination, which in turn improves metabolic balance and nutrient-use efficiency. These findings highlight a soil microbiome-mediated pathway linking fertilization strategy to crop physiological and chemical responses, providing mechanistic insights for sustainable fertilization management.